Peningkatan Safety Leadership terhadap Keselamatan Konstruksi di Industri Konstruksi pada Proyek Pembangunan Pengamanan Pantai di Pesisir Teluk Jakarta - Saputro, Widya Annas; Situmorang, Marningot Tua Natalis (Perhimpunan Sarjana Ekonomi dan Bisnis, 2025)
The Water Resources Construction Industry has experienced significant growth in meeting water needs and addressing hydrological hazards. However, this increase has also been accompanied by a rise in workplace accidents. To address this, shifting individual mindsets to a safety paradigm with a focus on safety behavior can enhance the Occupational Health and Safety (OHS) culture at the workplace. This study aims to analyze the impact of safety leadership on safety behavior, specifically in coastal protection projects involving high-risk work such as piling with specialized tools and methods. The study uses a qualitative method with a DO IT approach, collecting data through observations and interviews with project management of NCICD at PT.X. The main informants include the Project Manager, Site Administration Manager, Site Operation Manager, Site Engineering Manager, HSE Inspector, and Field Worker. Several indicators for measuring BBS include top management commitment, OHS regulations and procedures, worker communication, worker competence, and worker involvement. The study results show that the NCICD project has implemented enhanced safety leadership and BBS programs with strong management commitment. However, worker involvement in reviewing procedures and construction safety competence still needs improvement.